Development in multifocal contact lens design. Issue 12 (December 2020) - Retallic, Neil; Sugimoto, Keiji
Abstract : Neil Retallic and Keiji Sugimoto ask whether multifocal contact lens technology is keeping pace with the demands of the modern presbyope and introduces the novel design of the Miru monthly lens.